(untitled) (Al-Qamar, 2024)
Allah Almighty sent the Prophet (PBUH) with the Holy Quran, which guides us on how to solve problems at individual, social, national, and international levels. The Prophet (PBUH) is the epitome of guidance provided in the book of Allah. Therefore, the Ummah has preserved all aspects of the prophetic life in a collection called Fiqh al Sirah, so that we may overcome the hurdles and complications in our lives. Whenever ummah feels any hurdle in the way of social life, they seek guidance from the books written on the matter of Fiqh al Seerah. Water is a fundamental necessity of life that is bestowed upon us by Allah Almighty. The significance of water is not only emphasized in Islamic texts like the Quran, Hadith, and Fiqh but also in various scientific studies. However, in recent times, water pollution has become a major threat to human health and the environment. The contamination of natural water resources by various pollutants has led to severe consequences. To address this issue, it is crucial to understand the causes and impacts of water pollution. Some of the major causes of water pollution include industrial waste, domestic waste, and agricultural practices. To combat this issue, it is essential to adopt sustainable practices that reduce water pollution. This article aims to provide an in-depth analysis of the causes, impacts, and possible solutions to water pollution. The significance of this article is that it provides a comprehensive solution to the problem of water pollution, based on an in-depth analysis of the Islamic perspective extracted from Qyran, Seerah and Fiqh on environmental conservation.